1998
DOI: 10.1007/bf03041988
|View full text |Cite
|
Sign up to set email alerts
|

Management der Chemotherapie-induzierten Emesis: Was ist Standard nach 20 Jahren klinischer Forschung?

Abstract: Further therapy improvements, especially concerning emesis and nausea on the days following chemotherapy, are necessary and are currently object of clinical research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2002
2002
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 171 publications
0
1
0
1
Order By: Relevance
“…None of the systematic reviews done so far (no inclusion of palonosetron) have clearly demonstrated superiority of one agent over another. These studies included a comparison of granisetron, ondansetron, tropisetron and dolasetron, using all studies as references rather than head-to-head trials [31], and meta-analyses of randomised trials comparing granisetron with ondansetron [32], granisetron or tropisetron with ondansetron [33]. A recently performed meta-analysis of more than 40 cisplatin and non-cisplatin based studies showed an equivalence of ondansetron and granisetron, a significant advantage for granisetron over tropisetron, and no clear advantage of ondansetron over tropisetron [34,35].…”
Section: Comparative Efficacy Of the Available 5-ht 3 -Receptor-antagmentioning
confidence: 99%
“…None of the systematic reviews done so far (no inclusion of palonosetron) have clearly demonstrated superiority of one agent over another. These studies included a comparison of granisetron, ondansetron, tropisetron and dolasetron, using all studies as references rather than head-to-head trials [31], and meta-analyses of randomised trials comparing granisetron with ondansetron [32], granisetron or tropisetron with ondansetron [33]. A recently performed meta-analysis of more than 40 cisplatin and non-cisplatin based studies showed an equivalence of ondansetron and granisetron, a significant advantage for granisetron over tropisetron, and no clear advantage of ondansetron over tropisetron [34,35].…”
Section: Comparative Efficacy Of the Available 5-ht 3 -Receptor-antagmentioning
confidence: 99%
“…In einigen randomisierten Studien erbrachte weder eine höhe-re i.v.-Initialdosis (>8 mg) noch eine mehrfache Applikation von Ondansetron pro Tag signifikante Vorteile [15]. Andere Autoren hingegen fanden durchaus eine Überlegenheit der höheren Ondansetron-Dosierung [2,4,5,6,7,14]. In den aktuellen Guidelines der Multinational Association of Supportive Care in Cancer (MASCC) und der American Society of Clinical Oncology (ASCO) wird mittlerweile mit dem höchsten Level of Evidence (LOE IA) die Tagesdosis von 1 x 8 mg Ondansetron i.v.…”
Section: Introductionunclassified